The transcription factor nurr1 exerts concentration-dependent effects on target genes mediating distinct biological processes - Johnson, Magen M.; Michelhaugh, Sharon K.; Bouhamdan, Mohamad; Schmidt, Carl J.; Bannon, Michael J. (Frontiers in Neuroscience, 2011)
The transcription factor nurr1 plays a pivotal role in the development and maintenance of neurotransmitter phenotype in midbrain dopamine neurons. Conversely, decreased nurr1 expression is associated with a number of dopamine-related CNS disorders, including Parkinson’s disease and drug addiction. In order to better understand the nature of nurr1-responsive genes and their potential roles in dopamine neuron differentiation and survival, we used a neural cellular background in which to generate a number of stable clonal lines with graded nurr1 gene expression that approximated that seen in DA cell-rich human substantia nigra. Gene expression profiling data from these nurr1-expressing clonal lines were validated by quantitative RT-PCR and subjected to bioinformatic analyses. The present study identified a large number of nurr1-responsive genes and demonstrated the potential importance of concentration-dependent nurr1 effects in the differential regulation of distinct nurr1 target genes and biological pathways. These data support the promise of nurr1-based CNS therapeutics for the neuroprotection and/or functional restoration of DA neurons.